Challenges of Teacher Training in Sex Education - María Luisa Preinfalk-Fernández (Revista Electrónica Educare)
This article identifies the existing gaps in sex education in the student population of the Center for Research in Teaching and Education of the National University of Costa Rica, and its purpose is to contribute to the decision-making process to improve training for these students. A questionnaire was applied, using a structured sample stratified by unequal clusters, to 242 regular undergraduate students. The margin of error was 1.5 % and the confidence level was 95%. Data was tabulated using the CSPRO software and analyzed with the R software. A focus group was also held with teachers in sexuality courses in order to reflect on the results of the questionnaire application. Data was analyzed through the Integral Sexuality Approach and suggests that students lack the information necessary to exercise healthy, safe, and violence-free sexuality. This condition leads them to high risk situations because of the rare or lack of contraceptive use and the practice of coitus interruptus and makes them experience fears and guilt when being sexually active. Students have low sexual autonomy, which makes them vulnerable to violent situations and gives them stereotypes and prejudices that lead them to discriminate others for their sexual orientation or to become victims. In general, they are unaware of their reproductive and sexual rights and, therefore, are not capable of demanding them. These indicators should warn teacher training institutions to improve and strengthen their sexual education processes.